Red trees [videorecording (DVD)] - Willer, Marina; Willer, Marina; Pigott-Smith, Tim (Contemporary classics (Cohen Media Group), 2018)
Traces Marina Willer's father's family journey from war-torn Prague to South America as one of only twelve Jewish families to survive Nazi occupation of their city.